Comparison of Ranson’s and Glasgow criteria with revised Atlanta in prediction of mortality in acute pancreatitis patients - Nambi, Deepa; Giridharan, Bhanumati (International Surgery Journal, 2019)
Background: To compare the performance of Ranson’s Score (RS) and Glasgow Score (GS) with Revised Atlanta Classification (RAC) in prediction of mortality, and to check their suitability to replace RAC for surgical intervention of gallstone induced acute pancreatitis (GAP). Methods: A hospital based prospective study was conducted between April 2014 and May 2017 with patients presenting with GAP. RS and GS was evaluated using data in first 24 hours and at 48 hours post admission. Patients were classified into mild, moderate and severe based on RAC at the time of hospital stay. Sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) were calculated for each scoring system. Receiver Operating Characteristics (ROC) curves for mortality, ICU admission, Organ Failure (OF) and Gallstone Recurrence (GR) were plotted and predictive accuracy of each scoring system was measured by the Area under Curve (AUC). AUC values were compared for statistical significance using De Long test. A p-value of <0.05 was considered statistically significant. Results: Of 81 patients, 15 patients had OF and local complication classified as SAP, with persistent OF (16.0%). The AUC for RS was consistently the highest for predicting mortality (0.943), recurrence of gallstone (0.766), ICU-admission (0.801) and OF (0.852). RS had high specificity (61.9%), PPV (88.2%), Accuracy (90.1%) for predicting mortality, recurrence of gallstone and OF. Glasgow criteria had high sensitivity (85.1%), NPV (79.4) in predicting ICU-admission. Conclusions: RS in comparable with RAC in predicting mortality, GR in patients with GAP and early referral for surgical intervention.